Carceral Repair: Methane Extraction in Lake Kivu, Rwanda. Issue 2 (1st September 2020) - Doughty, Kristin
Abstract: This article, based on ethnographic fieldwork in 2016–2019, examines methane extraction operations in Lake Kivu on the Rwanda/DRC border as a lens into understanding how energy futures in Africa are imagined and enacted within national projects of post-war reconstruction. In 2005, scientists suggested that the lake's dissolved methane risked oversaturation within the century. This spurred state-backed projects to simultaneously prevent a natural disaster and harness the methane to meet Rwanda's rising electrification needs. Two companies are currently building and operating methane-fuelled power plants. The article suggests that these energy projects, an integral part of the overall architecture of social repair in Rwanda, reproduce and generate forms of captivity and entrapment that are central to understanding the lived politics of 'carceral repair', a generation after genocide.